2020
DOI: 10.1089/whr.2020.0061
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Menstrual Cycle Phases on Neural Excitability in the Primary Somatosensory Cortex and Ankle Joint Position Sense

Abstract: Introduction: Ankle sprain (AS) is one of the most common injuries among women engaged in competitive sports and recreational activities. Many studies have shown that several factors contributing to AS are influenced by the menstrual cycle. Despite the finding that abnormal joint position sense (JPS) is one of the major risk factors of AS, the alteration of the JPS throughout the menstrual cycle and its associated neural mechanisms remain unclear. Objective: This study aimed to examine whether the menstrual cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
4
1
Order By: Relevance
“…In addition, a previous study comparing ankle joint position matching task learning between young adults and the elderly showed that learning occurred in the elderly, but not in young adults ( Madhavan and Shields, 2005 ). Furthermore, the average absolute error before stimulation for each stimulation condition in this study was smaller than that of previous studies ( Iandolo et al, 2018 ; Ikarashi et al, 2020 ) that measured joint position matching task similarly to the present study. These results suggest that the absolute error might not have changed in this study on young adults as the joint position sense function of the subjects was high from the beginning.…”
Section: Discussioncontrasting
confidence: 72%
“…In addition, a previous study comparing ankle joint position matching task learning between young adults and the elderly showed that learning occurred in the elderly, but not in young adults ( Madhavan and Shields, 2005 ). Furthermore, the average absolute error before stimulation for each stimulation condition in this study was smaller than that of previous studies ( Iandolo et al, 2018 ; Ikarashi et al, 2020 ) that measured joint position matching task similarly to the present study. These results suggest that the absolute error might not have changed in this study on young adults as the joint position sense function of the subjects was high from the beginning.…”
Section: Discussioncontrasting
confidence: 72%
“…Several studies that have linked lower limb proprioception and the menstrual cycle have concluded that the proprioception of healthy female athletes may vary throughout the menstrual cycle, decreasing their proprioceptive ability when hormone levels are lower, close to menstruation [ 30 , 31 ]. However, other studies suggest that this variation does not occur [ 32 ]. Different measurement joints (ankle or knee) and other aspects such as emotional and pain perception could be behind these differences.…”
Section: Discussionmentioning
confidence: 99%
“…34 Although menstrual hormonal changes do not affect proprioception, fluctuations in the serum level of oestrogen affect neural excitability in the primary somatosensory cortex, a possible risk factor for ankle sprains. 35 Generalized joint hypermobility describes a range of motion in joints that is beyond normal limits. With a prevalence of between 10% and 15%, it is more common among Asian people, females, and young adults.…”
Section: Introductionmentioning
confidence: 99%